Sino-Russian cooperation potential within the BRICS framework - V. Ya. Vorobiev (Международная аналитика, 2016)
The article describes history of the BRICS group and its activities as a phenomenon of new multipolar world order. It studies Sino-Russian interactions in the BRICS against the background of Beijing’s foreign policy. The aim of China in international affairs, in the author’s opinion, is to avoid spoiling relations with any country and to secure the status of the second global superpower. The global balance of power is being increasingly determined not by West vs. Non-West opposition, but by new rivalry-conjugation: USA vs. China.